2005
DOI: 10.1086/427877
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neopterin, an Immune Activation Marker, Independently Predicts Disease Progression in Advanced HIV-1 Infection

Abstract: Soluble markers of immune activation add prognostic information to CD4 counts and viral load for risk of disease progression in advanced HIV-1 infection. The robust performance of neopterin, an inexpensive and reliably measured serum marker, supports its potential suitability for patient monitoring, particularly in resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 36 publications
4
66
0
3
Order By: Relevance
“…It may assist future studies that seek a more robust surrogate, pending its availability and cost. 24,25 The study had several limitations. First, our study was a sin- gle-centre cross-sectional observational study.…”
Section: Discussionmentioning
confidence: 99%
“…It may assist future studies that seek a more robust surrogate, pending its availability and cost. 24,25 The study had several limitations. First, our study was a sin- gle-centre cross-sectional observational study.…”
Section: Discussionmentioning
confidence: 99%
“…Neopterin has been reported as a sensitive marker of cell-mediated immune activity (3). Elevated plasma levels of neopterin have been detected in association with cancers (18), during sepsis (3) and numerous infections, including febrile neutropenia (15) and human immunodeficiency virus infection (14), hepatitis B-related chronic liver disease (7), and atherosclerosis (20). Serum neopterin levels have also been reported to correlate with disease activity in JDM patients (4).…”
Section: Discussionmentioning
confidence: 99%
“…It is known to be a marker of inflammation associated with cell-mediated immunity in various diseases (7,14,15,18,20). In our institution, we had observed that patients with a confirmed diagnosis of HLH had very high serum neopterin levels.…”
mentioning
confidence: 80%
“…It is produced by macrophages stimulated by the interferon-γ (IFN-γ), of which activated Th1-type lymphocytes are a source. Viral antigens, by the stimulation of IFN-γ production, cause the increase of neopterin concentrations in serum, and this concentration does not depend on the kind of the virus and it could serve as non-specific marker of viral infection (4)(5)(6)(7). In contrast to highly increased neopterin concentrations in patients with virus infections, in patients with acute bacterial infections usually normal or slightly increased values can be detected.…”
Section: Introductionmentioning
confidence: 99%